Synthesis,characterization and reactivity of mixed-metal cluster carbonyls. - Shawkataly, Omar (Universiti Sains Malaysia, 2017)
Series of RU3(CO)g(arphos)(L) complexes where L = PCY3. PPh3. P(C6H4F-mh, P(C6H4F-ph. P(C6H4CIph and PPh(C6H40Me-ph. and complexes of the type LAuCI where L= AS(C 21H2rP). AS(C21H21-m), Ph2As(CH2hAsPh2 and As(C30H21 ) were synthesized and characterized by spectroscopic and analytical techniques. The molecular structures of complexes have been determined by single X-ray diffraction analysis. The geometry structural and reactivity of the complexes are discussed. The elongation of Ru-Ru bonds within the RU3(CO)g(arphos)(L)is controlled by steric interaction between the group 15 monodentate ligand and CO on the adjacent Ru atom. Besides, the electronic effects accounting for this phenomenon are discussed. The Ru-P bond lengths can be attributed to the different electronic and the size of the cone angle.